Late pleistocene-holocene caldera-forming explosive volcanism of the Great Kuril arc - Smirnov S.Z.; Kotov A.A.; Bergal-Kuvikas Olga; Degterev A.V. (My University, 2025)
Caldera-forming explosive volcanism is the most dangerous natural hazard, which has catastrophic consequences to the life, humans and their economic activities. The paper presents a summary of published and original data on the late Pleistocene-Holocene caldera-forming volcanism within the Great Kuril Arc (GKA) available to the recent times. The published data reveal that formation of explosive calderas occurred throughout all GKA segments in the late Pleistocene and Holocene. Most frequent it was in the Southern and Central segments of GKA, where it meets the back arc Kuril Basin. The majority of the studied calderas appeared in the late Pleistocene 50–12 Ka and early Holocene 8–6 Ka. Intensive caldera-forming volcanism in GKA could be contemporaneous to similar events in the East-Kamchatka Volcanic Belt and Southern Kamchatka. Caldera eruptions of GKA in the late Pleistocene and early Holocene were linked to evolution of large reservoirs of predominantly dacitic magmas, which were generated by partial melting of metabasitic protholiths in the shallow crust (3–12 km) at 810–930°C. Rhyolitic melts of these magmas were saturated with H2O, CO2, sulfur compounds, and probably other gaseous species. This caused shallow degassing at the pre-eruptive stages of the magma reservoir evolution. The study rises problems, which solution would provide a basis for effective prediction of catastrophic volcano explosions and monitoring of active GKA caldera volcanoes.
Keywords: 38.37.25 Вулканология; Пик Креницина; Львиная Пасть; Медвежий; Пик Немо; Cenozoic::Quaternary::Holocene; Cenozoic::Quaternary::Pleistocene::Neopleistocene; Кайнозой::Четвертичная::Голоцен; Кайнозой::Четвертичная::Плейстоцен::Неоплейстоцен